Nearly Soft Menger Spaces - Tareq M. Al-shami; Ljubiša D. R. Kočinac (Journal of Mathematics)
In this paper, we define a weak type of soft Menger spaces, namely, nearly soft Menger spaces. We give their complete description using soft s-regular open covers and prove that they coincide with soft Menger spaces in the class of soft regular⋆ spaces. Also, we study the role of enriched and soft regular spaces in preserving nearly soft Mengerness between soft topological spaces and their parametric topological spaces. Finally, we establish some properties of nearly soft Menger spaces with respect to hereditary and topological properties and product spaces.